The Effect of Schema Therapy Combined with Neurofeedback Therapy on Cognitive Performance and Emotional Regulation in Children with ADHD - Memari, Samira; Dinarvand, Zahra (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to examine the effectiveness of schema therapy combined with neurofeedback therapy on cognitive performance and emotional regulation in children with Attention-Deficit/Hyperactivity Disorder (ADHD).Methodology: This study employed a randomized controlled trial (RCT) design with 30 children diagnosed with ADHD from psychological and neurological clinics in Tehran. Participants were randomly assigned to either the experimental group (n = 15), receiving schema therapy combined with neurofeedback therapy, or the control group (n = 15), receiving no intervention. The intervention was conducted over 12 weeks with two sessions per week, followed by a five-month follow-up period. Cognitive performance was assessed using the Wechsler Intelligence Scale for Children-Fourth Edition (WISC-IV), and emotional regulation was measured using the Emotion Regulation Checklist (ERC). Data were analyzed using repeated measures ANOVA and the Bonferroni post-hoc test in SPSS-27, with significance set at p < 0.05.Findings: The results indicated that the experimental group showed significant improvements in both cognitive performance (F(2, 56) = 18.47, p < 0.001) and emotional regulation (F(2, 56) = 22.31, p < 0.001) compared to the control group. Post-hoc analyses revealed that the experimental group’s cognitive and emotional scores significantly increased from baseline to post-test (p < 0.001) and remained significantly higher at follow-up (p < 0.001), while no significant changes were observed in the control group.Conclusion: The findings suggest that schema therapy combined with neurofeedback therapy is an effective intervention for improving cognitive performance and emotional regulation in children with ADHD.